Pemanfaatan Media Sosial Untuk Pemasaran Tanaman Hias Di Green Whispers Plants Nursery Lippo Plaza Kota Manado - Fikri Maulana Tahir; Mex Frans Lodwyk Sondakh; Grace Adonia Josefina Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2026)
Ornamental plants are one of the horticultural commodities with high economic value with promising business opportunities along with increasing consumer demand. The development of digital technology encourages business actors to utilize social media as an effective marketing tool. This study aims to describe the use of social media in marketing ornamental plants at Green Whispers Plants Nursery, Lippo Plaza, Manado City. The research method used is descriptive with purposive sampling technique. Based on the results and discussion, it can be concluded that the use of social media for marketing at Green Whipers Plants Nursery, Lippo Plaza, Manado City has been proven to be practical and effective in simplifying the marketing process, reaching a wider market without distance and time limitations, providing clear product information, and increasing sales and profits.